Experimental investigations on mechanical strength of concrete using nano-alumina and nano-clay. (2022) - Sargunan, K.; Venkata Rao, M.; Alex Rajesh, A.; Babu, R.; Prasanthni, P.; Jagadeep, K.; Rinawa, Moti Lal
Abstract: The current work aims to advance the mechanical characteristics of concrete by replacing cement with a low volume fraction of nano-alumina particles and fine aggregate with nano-clay. The initial tests had piloted on the conventional concrete using varying fractions of nano-alumina particles in order to determine the optimal nano-alumina proportions for various curing times (1 week, 4 weeks, and 8 weeks). Then, the accompanying experiments using varied volume fractions of nano-clay with the determined optimal proportion of concrete nano-mixture were conducted. The results indicated that the optical volume percentage in the concrete nano-mixture should be 2.0 percent nano-alumina particles and 3.0 percent nano-clay in order to achieve the greatest splitting tensile strength, and compressive strength. With the assistance of nano-alumina particles and nano-clay, the mechanical characteristics of the concrete were improved by around 30% effectively.